From "Powder Monkey" to Certified Explosives Technician: A Position Paper - Gregory S. Parker (International Society of Explosives Engineers, 1995)
The explosives community has seen tremendous technological advances during the past several decades. When this industry was in it's infancy and even past, Powder Monkey's defied the odds by relying on daring and cunning to unleash the power contained in nitroglycerin and black powder. Unlike the manufactured improvements, there has been little in professional evolution amongst the blasting fraternity unless provoked (for the most part) by the government. It is the intent of this author to advance the cause of an industry wide training and certification program, uniform in nature and broad-based enough to be voluntary, giving states whose outstanding programs are already in place, the opportunity to provide input. In creating this type of atmosphere, grandfathering, reciprocity and accessibility would be paramount. With ISEE taking a firm leadership role during the inception and NICET's involvement in the administration, the idea postulated here is intended to spark interest and debate, bringing the inception of such a program to the forefront.